Water line positions in the 782–840 nm region. (October 2015) - Hu, S.-M.; Chen, B.; Tan, Y.; Wang, J.; Cheng, C.-F.; Liu, A.-W.
Abstract: A set of water transitions in the 782–840 nm region, including 38 H2 16 O lines, 12 HD 16 O lines, and 30 D2 16 O lines, were recorded with a cavity ring-down spectrometer calibrated using precise atomic lines. Absolute frequencies of the lines were determined with an accuracy of about 5 MHz. Systematic shifts were found in the line positions given in the HITRAN database and the upper energy levels given in recent MARVEL studies. Abstract : Highlights: Cavity ring-down spectra of H2 16 O, HD 16 O, and D2 16 O lines in the 782–840 nm region were measured. Absolute line positions of 80 water lines were determined with an accuracy of about 5 MHz. The H2 16 O positions given in HITRAN have a systematic shift of 0.001 cm −1 in the 796–840 nm region. MARVEL D2 16 O energies have a systematic deviation of about −0.008 cm −1 .